Energy services at local and national level in the transition period in Hungary - Pál Valentiny (Hungarian Academy of Sciences, Institute of Economics, 2008)
Energy industries are mainly organised at national level in Hungary, however local governments have their specific role in the system. Local governments have been major performers in the first period of the transition process: they were entitled to receive 25 per cent of the shares in electric utilities and 40 per cent of the shares in gas supply during the privatisation process. They did not build up long standing portfolios in these utilities. They became more important players at district heating, where they have a contradictory triple function - owner, regulator and provider of the local social safety net. Local governments are also in the forefront of the energy saving programmes.
Keywords: L43; L51; L97; Q48; 330; energy industries; regulation; local governments; Energiewirtschaft; Regionalverwaltung; Kommunale Energiewirtschaft; Regulierung; Systemtransformation; Ungarn